Field notes contributed by James J. Dinsmore regarding miscellaneous bird sightings, summer 2003 - Dinsmore, James J.et al (2003)
Field notes contributed by James J. Dinsmore includes miscellaneous bird sightings at multiple locations reported by Bruce Ehresman, Pat Schlarbaum, Douglas C. Harr and others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 2003. Epson - sheet feed